The concept of land use and protection in modern conditions of social development of Ukraine - Dorosh, Y.; Ibatullin, S.; Barvinskyi, A.; Tarnopolskyi, A.; Sakal, O. (Land Management, Cadastre and Land Monitoring, 2021)
The crisis situation in the use of land resources in both agrarian and non-agrarian spheres of land use in Ukraine is stated. One of the main reasons for this situation is identified the lack of a perfect system of legal documents that would really regulate scientifically sound environmentally and economically acceptable land use. The concept of land use and protection in the conditions of development of the digital economy and society in Ukraine which can be used for development of the corresponding state target program is substantiated. The concept defines the guiding direction in the organization and implementation of processes of sustainable land use, protection of lands from depletion, degradation and pollution in market conditions with high priority of monitoring of land and land relations by automated information-analytical systems and remote sensing of the Earth. The principles and approaches to the development of the state target program of land use and protection are proposed. Options for solving the problem of ensuring the rational use and protection of land are outlined and analysed. The directions, ways, stages of realisation, innovative component and expected results and efficiency of execution of the state target program of use and protection of lands on the basis of the developed concept are defined. Keywords: land resources, rational use of land resources, land monitoring, land and soil protection measures